Exploring Challenges of Indonesian EFL Teachers in Implementing Differentiated Instruction in ELT Classroom - Laksono, Kukuh; Rohimah, Nadya Khansa; Fauziati, Endang (Institut Agama Islam Negeri Madura, 2024)
Differentiated instruction (DI) as a method of the Merdeka curriculum in Indonesia may be problematic for the teacher when implementing it in the classroom. This study investigates Indonesian EFL (English as a Foreign Language) teachers' perspectives regarding implementing Differentiated Instruction in their classrooms. Through qualitative analysis, this research identifies the teachers' challenges and explores the strategies for implementing DI. Semi-structured interviews were used to reveal the challenges and strategies teachers used DI. The collected data were then analyzed qualitatively with the thematic analysis used in this study in analysis of the data. Findings reveal that teachers view DI as important for addressing student diversity, enhancing engagement, and improving academic outcomes. However, significant challenges include adapting learning materials, managing time constraints, and varying readiness levels among teachers and students. Despite their belief that DI is very positive, some challenges highlight how to adopt DI properly; professional development, resource allocation, and strategic planning are essential